Frege's 'On the Concept of Number' (1891) – an unnoticed publication. Issue 4 (3rd July 2016) - Sullivan, David
ABSTRACT: A short piece by Frege, heretofore overlooked, containing a précis of his views on the concept of number, is presented, after some very brief questions about Frege's possible involvement in the wider intellectual milieu.